(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research aims to know the impact of the innovative matrix strategy and the problem tree strategy in teaching mathematics to intermediate grade female students on mathematical proficiency. To achieve the research objectives, an experimental approach and a quasi-experimental design were used for two equivalent experimental groups. The first is studied according to the innovative matrix strategy, the second group is studied according to the problem tree strategy. The research sample consisted of (32) female students of the first intermediate grade, who were intentionally chosen after ensuring their equivalence, taking into several factors, most notably (chronological age, previous achievement, and intelligence test). The research tools consisted of test of mathematical proficiency with its four components: (conceptual comprehension, Procedural fluency, strategic competence, and adaptive reasoning) and a scale for the fifth component, which is productive desire.